Preparação e caracterização de nanocompósitos de LDPE e LDPE/EVA com partículas de Ag/TIO2 para aplicações antimicrobiais - Olyveira, Gabriel Molina de (Universidade Federal de São Carlos, 2009)
This study investigated the use of a charger inorganic (titanium dioxide) as a support for silver nanoparticles and evaluated the use of material obtained as filler in polymer for antimicrobial application.Silver nanoparticles-titanium dioxide were synthesized by the reduction method developed by Turkevich, also known as a method of citrate. Therefore, we used three different types of titanium dioxide in the colloidal synthesis and found that nanometer titanium dioxide showed better results for the deposition of silver nanoparticles. Silver Nitrate was reduced by sodium citrate with and without the presence of a surfactant (PVP-Polyvinylpyrrolidone) resulting in a stable suspension of nanoparticles of silver / titanium dioxide. We also tested NH4OH (ammonium hydroxide) to prevent the growth of nanoparticles during the reaction. Nanocomposite of LDPE and LDPE / EVA were produced by mixing in the molten state with the Ag nanoparticles-titanium dioxide resulting from the colloidal synthesis. By assessing the rheological, thermal and morphological analysis we found that compared with nanocomposite LDPE / EVA, LDPE nanocomposite showed better results with regard to dispersion of the charges, but nanocomposite LDPE / EVA showed better results in antimicrobial assays due to the polar nature the grouping of EVA able to bind more easily to inorganic fillers.
Preparation and characterization of NANOSILVER/TITANIUM dioxide particles for application in lDPE composites with antimicrobial activity
Keywords: Polímeros; Nanocompósitos; Antimicrobiana; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA